Foreign Direct Investment in Emerging Markets: Evidence from Russia since the 2000s - Mahir Suleymanov (Charles University in Prague, Institute of Economic Studies (IES), 2021)
This paper aims to analyze the role of FDI inflow in the Russian economy and determine the degree of impact on the economic growth rate. The empirical research captures 2000-2019 years specifying by quarterly time-series. Although, in general, it is considered that the FDI can transmit technology and development to the host country, but this paper shows that in the case of Russia, the role of FDI inflow into the country has an endogenous component, which does not exert a robust impact on the economic growth.
Keywords: F21; F43; 330; Foreign Direct Investment; economic growth; transition economies; Endogeneity